2012
DOI: 10.3389/fmicb.2012.00035
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Resource Chemistry on the Composition and Function of Stream Hyporheic Biofilms

Abstract: Fluvial ecosystems process large quantities of dissolved organic matter as it moves from the headwater streams to the sea. In particular, hyporheic sediments are centers of high biogeochemical reactivity due to their elevated residence time and high microbial biomass and activity. However, the interaction between organic matter and microbial dynamics in the hyporheic zone remains poorly understood. We evaluated how variance in resource chemistry affected the microbial community and its associated activity in e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
12
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(13 citation statements)
references
References 54 publications
1
12
0
Order By: Relevance
“…The present work extends current knowledge about the structure and community composition of bacterial communities in lake and rivers, as the knowledge available about these communities in freshwater biofilm is very limited Hall et al, 2012;Bricheux et al, 2013). First, we have shown that river and lake bacterial communities displayed some common features in their overall structure (like the dominance of Proteobacteria, in particular of Alphaproteobacteria), but also differed by the relative contribution of Actinobacteria and Gammaproteobacteria to these communities.…”
Section: Discussionsupporting
confidence: 56%
“…The present work extends current knowledge about the structure and community composition of bacterial communities in lake and rivers, as the knowledge available about these communities in freshwater biofilm is very limited Hall et al, 2012;Bricheux et al, 2013). First, we have shown that river and lake bacterial communities displayed some common features in their overall structure (like the dominance of Proteobacteria, in particular of Alphaproteobacteria), but also differed by the relative contribution of Actinobacteria and Gammaproteobacteria to these communities.…”
Section: Discussionsupporting
confidence: 56%
“…Few studies have addressed structure-function coupling of hyporheic microorganisms (12,19), which our study expands now by showing the apparent need to consider the active rather than the bulk community. No clear relationship between community structure and function existed when the starter community was omitted from the analysis, indicating that the observed relationship is driven by the temporal dimension in our experiment.…”
Section: Planctomyces Gemmatamentioning
confidence: 63%
“…Samples for bulk microbial biomass were harvested from the glass beads by sonication and vortexing, and C and N content was determined using an elemental analyzer (EA1110; CE Instruments, ThermoFisher) (19). An extra sample of glass beads was collected into sterile vials containing 5 ml formaldehyde (2.5%) pending further processing for cell counts.…”
Section: Methodsmentioning
confidence: 99%
“…The alignment used in AmpliconNoise differs from traditional sequence alignment in that it requires the use of doubleprecision floating-point operations when performing alignment score calculation. AmpliconNoise is used to denoise the 454 data in order to reduce the overestimation of the number of unique taxonomic units implied by the data, a common problem in metagenomic sequencing [11]- [19].…”
Section: Previous Workmentioning
confidence: 99%